(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the differences in the solvency ratios of PT Tempo Scan Pacific Tbk before and after the COVID-19 pandemic. This research employed a comparative quantitative approach using secondary data obtained from the company’s financial statements for the period 2018–2022. Data analysis was conducted using the Independent Sample t-Test with the assistance of SPSS version 22. The results showed that the significance value of DAR was 0.819 (> 0.05) and the significance value of DER was 0.968 (> 0.05). These findings indicate that there were no significant differences in the solvency ratios before and after the COVID-19 pandemic. Therefore, the pandemic did not significantly affect the company’s solvency condition. PT Tempo Scan Pacific Tbk was able to maintain financial stability and a balanced capital structure during the periods before and after the pandemic.